Evaluation of the World Bank Group's Activities in the Extractive Industries : Factoring in Governance - Thomas, M.A. (World Bank, Washington, DC, 2014)
This paper examines the links between governance and the Extractive Industries sector, and considers the implications of those links for the work of the World Bank. This evaluation takes place on the heels of important complementary World Bank initiatives, upon which it draws. The Bank has pioneered a research initiative into the economics of civil war crime and violence, which considered inter alia the effects of natural resource endowments. A task force has examined the special problems of Low Income Countries Under Stress. There is overlap between this group of countries and the group of resource-rich Bank borrowers. And the Bank has done substantial research linking governance to development outcomes.